Application of Gray Relation Analysis for Multi-Response Optimization of Plasma Heat Assisted Turning Performance - Babu Rao, Thella; Pilli, Venu; Revanth Sai Venkat, Nallamotu; Pavan, Nagandla; Shiva Ram, Thalari (International Journal of Engineering and Technology, 2018)
This paper presents optimization of plasma heat assisted turning process for machining hardened EN24 die steel (53HRC) by using gray relational analysis. Flank wear and surface roughness (Ra) are experimentally measured as the process performance characteristics under varying conditions of preheating temperature, cutting speed and cutting length. The plasma heating approach was implemented to preheat the workpiece. The machining experiments were conducted according to the L16 design of experiments. Since the chosen machining performance indicators are found with confliction for the chosen process variables, the problem is treated as multi-response optimization problem to minimize the tool wear and surface roughness simultaneously. Therefore, the problem was solved by implementing the gray relational analysis and the derived optimal machining conditions were analysed and reported.Â Â
Keywords: Plasma heat assisted turning; flank wear; surface roughness; EN24 die steel; Gray relational analysis.